À=-39x2+46x2-52x2-114x2A = - 39x² + 46x² - 52x² - 114x²
A = - 39x² - 52x² -114x² + 46x²
A = - 205x² + 46x²
A = - 159x²
B=9x2-11x+4x-16x2-x2
B = 9x² - 11x + 4x - 16x² - x²
B = 9x² - 16x² - x² - 11x + 4x
B = - 8x² - 7x
C=3x2-5x+x2-5+4x-9
C = 3x² + x² - 5 + 4x - 9
C = 4x² + 4x - 14
D=-11x-x2-5+13x+9x2-2x+9
D = - 11x - x² - 5 + 13x + 9x² - 2x + 9
D = - x² + 9x² - 11x - 2x + 13x - 5 - 9
D = 8x² - 14
E=3a2-2a+5-7a-11a2+1
E = 3a² - 2a + 5 - 7a - 11a² + 1
E = 3a² - 11a² - 2a - 7a + 5 + 1
E = - 8a² - 9a + 6